Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Plz help me out i am helpless...... answer is (2) option that is 0

Plz help me out i am helpless...... answer is (2) option that is 0

Question Image
Grade:11

1 Answers

ROSHAN MUJEEB
askIITians Faculty 829 Points
one year ago
Dear Student
f(x) = (1-x)^n
f’(x) = -n(1-x)^n-1
f’’(x) = +n(n-1)(1-x)^n-2
And so on
When you put x=0
f(0) = 1
f’(0) = -n
f’’(0) = n(n-1)/2
The pattern as you observe ..The terms are nC0 –nC1 + nC2+...
This the binomial expansion of (1-x)^n when x=1, so the ans is 0
Hope you got it

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free